Legal Assistance of Micro, Small and Medium Enterprises Through the Online Single Submission (OSS) System in the Brawijaya Dairy Industry (BRADY) Milk Processing Business in Malang - WAHYUNI, Endang Dwi; LENIWATI, Driana; SETYAWAN, Setu (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
This service was carried out at CV Brawijaya Dairy Industry (BRADY). BRADY is one of the MSMEs in Malang Regency that does business in the field of milk processing; the products produced are mozzarella cheese and fermented milk products (yogurt). The business has been carried out well, and the product quality is in accordance with consumer desires. However, until now, the Company still needs a Business Identification Number. The Business Identification Number (NIB) is an identification mark for business actors, both individual and non-individual businesses, as well as a commercial or operational permit. A NIB can be obtained online through the Online Single Submission System (OSS). In addition, Brady also does not have halal certification; one of the obstacles is that Brady needs an NIB. Halal certification is essential for developing his business because product marketing is hampered by the Company needing to have halal certification, so many prospective consumers or distributors do not want to accept Brady products because they are not halal certified. By having business legality, in addition to the Company being better known to the public, the Company also gets certainty and business protection. Other benefits include more accessible access to business assistance from the government, easier access to business capital, and the opportunity to obtain empowerment assistance from the government.